PENINGKATAN KEMAMPUAN MENULIS CERITA FANTASI MENGGUNAKAN MODEL MIND MAPPING PADA SISWA KELAS VII A SMP NEGERI 24 TANJUNG JABUNG TIMUR TAHUN AJARAN 2018/2019 - Muslimin Muslimin; Abdoel Gafar; Firman Tara (Aksara: Jurnal Ilmiah Pendidikan Bahasa dan Sastra Indonesia, 2019)
The purpose of this study was to describe the ability of students to write fantasy stories using the Mind Mapping model in class VII. A students at SMP Negeri 24 Tanjung Jabung Timur Academic Year 2018/2019. The type of research used was class action research and analyzed descriptively. The research subjects were all students of class VII.A with a total of 21 people consisting of 10 men and 11 women. The study uses total sampling. Data collection techniques are carried out with non-tests and tests. Data were analyzed using qualitative analysis techniques, using criteria scales and analyzed results presented in the form of numbers and explained in the form of a description. Based on the analysis carried out, it was obtained that the average value in cycle one was 69.28 enough but did not meet the minimum completeness criteria (KKM) Indonesian subjects for individual completeness were 73, while the average value in the second cycle was 80, 57 is good and has met the minimum completeness criteria (KKM) of Indonesian language subjects. Thus the Mind Mapping model can be used in learning to write fantasy stories. Keywords: writing, fantasy story, mind mapping model